Topological flat bands in a family of multilayer graphene moiré lattices - Dacen Waters; Ruiheng Su; Ellis Thompson; Anna Okounkova; Esmeralda Arreguin-Martinez; Minhao He; Katherine Hinds; Kenji Watanabe; Takashi Taniguchi; Xiaodong Xu; Ya-Hui Zhang; Joshua Folk; et al. (Nature Communications)
Abstract Moiré materials host a wealth of intertwined correlated and topological states of matter, all arising from flat electronic bands with nontrivial quantum geometry. A prominent example is the family of alternating-twist magic-angle graphene stacks, which exhibit symmetry-broken states at rational fillings of the moiré band and superconductivity close to half filling. Here, we introduce a second family of twisted graphene multilayers made up of twisted sheets of M- and N-layer Bernal-stacked graphene flakes. Calculations indicate that applying an electric displacement field isolates a flat and topological moiré conduction band that is primarily localized to a single graphene sheet below the moiré interface. Phenomenologically, the result is a striking similarity in the hierarchies of symmetry-broken phases across this family of twisted graphene multilayers. Our results show that this family of structures offers promising new opportunities for the discovery of exotic new correlated and topological phenomena, enabled by using the layer number to fine tune the flat moiré band and its screening environment.